Comparison Between Single-Use Flexible Ureteroscope and Reusable Flexible Ureteroscope for Upper Urinary Calculi: A Systematic Review and Meta-Analysis - Meng, Chunyang; Peng, Lei; Li, Jinze; Li, Yunxiang; Li, Jinming; Wu, Ji (Frontiers in Surgery, 2021)
Objective: This article explores the differences in the effectiveness and safety of the treatment of the upper urinary calculi between single-use flexible ureteroscope (su-fURS) and reusable flexible ureteroscope (ru-fURS). Methods: We systematically searched PubMed, Embase, Cochrane Library, Scopus database, and CNKI databases within a period from the date of database establishment to November 2020. Stata 16 was used for calculation and statistical analyses. Results: A total of 1,020 patients were included in the seven studies. The statistical differences were only found in the Clavien–Dindo grade II postoperative complication [odds ratio (OR) 0.47; 95% CI 0.23–0.98; p = 0.04]. No significant statistical differences were observed in operative time (OT), estimated blood loss (EBL), length of hospital stay (LOS), and stone-free rate (SFR). Conclusion: Our meta-analysis results demonstrate that su-fURS, compared with ru-fURS, has similar effectiveness and better security for treating upper urinary calculi.